2005
DOI: 10.1172/jci23486
|View full text |Cite
|
Sign up to set email alerts
|

TWEAK induces liver progenitor cell proliferation

Abstract: Progenitor ("oval") cell expansion accompanies many forms of liver injury, including alcohol toxicity and submassive parenchymal necrosis as well as experimental injury models featuring blocked hepatocyte replication. Oval cells can potentially become either hepatocytes or biliary epithelial cells and may be critical to liver regeneration, particularly when hepatocyte replication is impaired. The regulation of oval cell proliferation is incompletely understood. Herein we present evidence that a TNF family memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
357
3
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 372 publications
(380 citation statements)
references
References 53 publications
16
357
3
1
Order By: Relevance
“…OV6/CK19/Rab3b + hepatic progenitors may be more susceptible to the microenvironment, rendering growth of these cells in culture more fastidious. A recent study has demonstrated that a TNF family member called TWEAK (TNF-like weak inducer of apoptosis) specifically stimulated endogenous hepatic oval cell proliferation both in vivo and in vitro [53]. This selective mitogen may provide a valuable tool to discriminate between endogenous and HSCs-derived hepatic progenitor cells as well as potentially permitting expansion of the former in culture.…”
Section: Discussionmentioning
confidence: 99%
“…OV6/CK19/Rab3b + hepatic progenitors may be more susceptible to the microenvironment, rendering growth of these cells in culture more fastidious. A recent study has demonstrated that a TNF family member called TWEAK (TNF-like weak inducer of apoptosis) specifically stimulated endogenous hepatic oval cell proliferation both in vivo and in vitro [53]. This selective mitogen may provide a valuable tool to discriminate between endogenous and HSCs-derived hepatic progenitor cells as well as potentially permitting expansion of the former in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Oval cells are derived from the canal of Hering, and in rodents this canal barely extends beyond the limiting plate ( Figures 4, 5); in contrast, in human liver the organization of the biliary tree is different, with the canal of Hering extending to the proximate third of the lobule [68] and so apparently requiring a name change from oval cells to 'hepatic progenitor cells' (HPCs) [69]. An enormous range of markers has been used to identify ovals cells (Table 2) [70][71][72][73][74][75][76][77][78][79][80][81][82][83] and some, such as Dlk, may signal imminent hepatocyte differentiation [71]. A popular experimental procedure to elicit an oval cell response in rats is to pre-treat the animals with 2-acetylaminofluorene (2-AAF) before performing a two-thirds PH (the 2-AAF/PH protocol).…”
Section: The Facultative Stem Cell Response: Oval/hepatic Progenitormentioning
confidence: 99%
“…Hedgehog (Hh) signalling acting through the receptor Patched (PTC) on oval cells/HPCs is required for their survival [76]. Perhaps most significantly, inflammatory cells produce a range of cytokines and chemokines that initiate the response [82,83]; SDF-1 attracts CXCR4 + T cells, and these cells express TNF-like weak inducer of apoptosis (TWEAK), which stimulates oval cell proliferation by engaging its receptor Fn14 [80]. Other elements of the inflammatory response that may stimulate oval cells include lymphotoxin-β, IFNγ , TNFα and even histamine [81].…”
Section: The Facultative Stem Cell Response: Oval/hepatic Progenitormentioning
confidence: 99%
“…In this respect, the 2005 report by Jakubowski and coworkers 8 was a milestone publication; it proposed a TNF family member, tumor necrosis factor-like weak inducer of apoptosis (TWEAK), as a direct LPC mitogen. Like most TNF superfamily ligands, TWEAK [also known as tumor necrosis factor (ligand) superfamily member 12, CD255, or previously APO3 ligand] is initially synthesized as a type II transmembrane protein that can be cleaved into a soluble cytokine.…”
mentioning
confidence: 99%
“…This hypothesized relationship between LPCs and Fn14 signaling was strengthened by experiments described by Jakubowski and coworkers. 8 In their study, it was demonstrated that hepatic TWEAK overexpression, after transgenic or adenoviral delivery, induces an LPC response; knockout (KO) of TWEAK/Fn14 inhibits the appearance of LPCs in an experimental model of oval cell proliferation. Furthermore, TWEAK directly induces proliferation of a biliary epithelial cell line with progenitor-like characteristics.…”
mentioning
confidence: 99%